(untitled) (Jurnal Tata Kelola Pendidikan, 2020)
The purpose of this study was to determine how effective the motion and song "Going To School" in improving the language skills of children aged 5-6 years in TK Pertiwi Banaran Kab. Nganjuk This research is a quantitative study with a pre-experimental design method showing that the motion and the song "Going to School" are effective for stimulating language skills of children aged 5-6 years in group B in TK Pertiwi Banaran Kab. Nganjuk The number of samples in this study were 21 children. Pretest results with an average value of 9.76, a maximum value of 14, and a minimum value of 5. While posttest results with an average value of 14.14, a maximum value of 20, and a minimum value of 4. Results of data analysis using Paired Test Sample T-Test with df = 20 shows a t table of 2.085 and a t-test value of 12.112. This shows t arithmetic> from the t table value so that the motion and the song "Go to School" are effective in stimulating language skills of children aged 5-6 years.